Factors Associated with Medical Students’ Readiness of Interprofessional Education Implementation: Findings from A Medical School in Indonesia - Flora Ramona Sigit Prakoeswa; Harun Joko Prayitno; Saiful Hidayat; Ratih Pramuningtyas; Erika Diana Risanti (Postgraduate, University of Mataram, 2025)
This study aimed to analyse factors affecting medical students’ readiness for interprofessional education (IPE) implementation. This is an observational cross-sectional study conducted at the Faculty of Medicine, Universitas Muhammadiyah Surakarta, Indonesia. We performed a total sampling approach targeting all medical students, inviting voluntary participation through online messages. Data collection utilised validated questionnaires: the Indonesian version of the Readiness for Interprofessional Learning Scale (RIPLS) and The Interdisciplinary Education Perception Scale (IEPS). All statistical analyses were performed using STATA-BE 18 software. Responses were obtained from 654 medical students, the majority (83.49%) being preclinical students. The mean RIPLS score was 67.28 ± 6.70, and the mean IEPS score was 63.09 ± 5.73. No statistically significant differences in RIPLS scores were found based on age, gender, or educational level. However, there was a significant difference in RIPLS scores between students who had experienced IPE education and those who had not (p-value=0.028). Exposure to IPE education significantly influences medical students' readiness for IPE implementation, regardless of demographic characteristics or educational level.